Ralstonia pickettii and Pseudomonas aeruginosa Bloodstream Infections Associated With Contaminated Extracorporeal Membrane Oxygenation Water Heater Devices. (20th May 2022) - Baker, Meghan A; Rhee, Chanu; Tucker, Robert; Vaidya, Vineeta; Holtzman, Meghan; Seethala, Raghu R; Bentain-Melanson, Maria; Lenox, Jesslyn; Smith, Adam R; Gassett, Allison; Huntley, Miriam; Sater, Mohamad; et al.
Abstract: We report on probable factory-based contamination of portable water heaters with waterborne pathogens and 2 bloodstream infections potentially attributable to off-label use of these water heaters to warm extracorporeal membrane oxygenation circuits. Great caution is warranted when using water-based devices to care for critically ill patients.